1161 Central nervous system tumours and agricultural exposures in the prospective cohort agrican. (24th April 2018) - Piel, Clément; Pouchieu, Camille; Tual, Séverine; Migault, Lucile; Lemarchand, Clémentine; Carles, Camille; Boulanger, Mathilde; Gruber, Anne; Rondeau, Virginie; Marcotullio, Elisabeth; Lebailly, Pierre; Baldi, Isabelle
Abstract : Studies in farmers suggest a possible role of pesticides in the occurrence of Central Nervous System (CNS) tumours but scientific evidence is still insufficient. Using data from the French prospective agricultural cohort AGRICAN (Agriculture and Cancer), we investigated the associations between exposure of farmers and pesticide users to various kinds of crops and animal farming and the incidence of CNS tumours, overall and by subtypes. Over the 2005–2007, 1 81 842 participants completed the enrollment questionnaire that collected a complete job calendar with lifetime history of farming types. Associations were estimated using proportional hazards models with age as underlying timescale. During a 5.2 years average follow-up, 273 incident cases of CNS tumours occurred, including 126 gliomas and 87 meningiomas. Analyses showed several increased risks of CNS tumours in farmers, especially in pesticide users (hazard ratio=1.96; 95% confidence interval: 1.11–3.47). Associations varied with tumour subtypes and kinds of crop and animal farming. The main increases in risk were observed for meningiomas in pig farmers and in farmers growing sunflowers, beets and potatoes and for gliomas in farmers growing grasslands. In most cases, more pronounced risk excesses were observed among pesticide applicators. Even if we cannot completely rule out the contribution of other factors, pesticide exposures could be of primary concern to explain these findings.